2023
DOI: 10.3390/md21070398
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Polyunsaturated Fatty Acid Eicosapentaenoic Acid or Docosahexaenoic Acid Improved Ageing-Associated Cognitive Decline by Regulating Glial Polarization

Abstract: Neuroinflammation induced by microglial and astrocyte polarizations may contribute to neurodegeneration and cognitive impairment. Omega (n)-3 polyunsaturated fatty acids (PUFAs) have anti-inflammatory and neuroprotective effects, but conflicting results were reported after different n-3 PUFA treatments. This study examined both the change in glial polarizations in ageing rats and the differential effects of two omega-3 PUFAs. The results showed that both PUFAs improved spatial memory in ageing rats, with docos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…190 EPA and DHA are able to improve cognitive problems by inhibiting neuroinflammation caused by the overactivation of M1 microglia, decreasing the expression of C3 in the brain, and the proBDNF/p75 pathway. 2…”
Section: Dietary Lipids the Gba And Cognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…190 EPA and DHA are able to improve cognitive problems by inhibiting neuroinflammation caused by the overactivation of M1 microglia, decreasing the expression of C3 in the brain, and the proBDNF/p75 pathway. 2…”
Section: Dietary Lipids the Gba And Cognitionmentioning
confidence: 99%
“…1 It has been reported that n-3 polyunsaturated fatty acids (n-3 PUFAs), as essential lipids, significantly alleviate memory impairments. 2 Conversely, mice fed a high saturated fat diet have been observed to exhibit significant cognitive decline. 3 Distinct dietary lipids exert diverse impacts on cognition and brain health.…”
Section: Introductionmentioning
confidence: 99%
“…Marine algae are rich in polyunsaturated fatty acids (PUFAs), with omega-3 polyunsaturated fatty acids (ω-3 PUFAs) as their main constituent [ 255 ]. The ω-3 PUFAs are essential for regulating the structural features of immune and neural cellular membranes [ 256 ]. The two main forms of ω-3 polyunsaturated fatty acids (PUFAs) that are produced by marine algae are the long-chained 22:6n-3 docosahexaenoic acid (DHA) 37 ( Figure 7 ) and 20:5n-3 eicosapentaenoic acid (EPA) 38 ( Figure 7 ), as well as its precursor alpha-linolenic acid (ALA) 39 ( Figure 7 ) [ 257 ].…”
Section: Marine Algaementioning
confidence: 99%
“…However, there are several preclinical studies in healthy and disease model animals. In healthy and aged rodents, diets supplemented with PUFAs improved their performance on several tests of memory, including spatial, object recognition, and associative memory [ 151 , 152 , 153 ]. DHA supplements seem to be more efficacious than EPA in improving memory and attenuating the proinflammatory cytokines associated with ageing [ 152 ].…”
Section: Cognitive Impairmentmentioning
confidence: 99%